Equilibrium in a Dynamic Limit Order Market - GOETTLER, RONALD L.; PARLOUR, CHRISTINE A.; RAJAN, UDAY (Journal of Finance, 2005)
ABSTRACT We model a dynamic limit order market as a stochastic sequential game with rational traders. Since the model is analytically intractable, we provide an algorithm based on Pakes and McGuire (2001) to find a stationary Markov‐perfect equilibrium. We then generate artificial time series and perform comparative dynamics. Conditional on a transaction, the midpoint of the quoted prices is not a good proxy for the true value. Further, transaction costs paid by market order submitters are negative on average, and negatively correlated with the effective spread. Reducing the tick size is not Pareto improving but increases total investor surplus.